BIẾN ĐỔI TRẠNG THÁI CHỨC NĂNG CƠ THỂ CỦA THỦY THỦ TÀU NGẦM SAU MỘT NĂM ĐI BIỂN - Hoàng, Văn Huấn; Bùi, Thị Hương; Nguyễn, Hồng Quang; Trần, Thị Nhài (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ASSESSMENT OF THE BODY FUNCTIONAL CHANGES OF SUBMARINERS ACCORDING TO TIME Submariner is a specific work with many adverse environmental factors. These factors constantly affect submariners leading to numerous physiological and psychological stressors so that the state of body function is reduced, occurring occupational disease and reducing work quality of submariners. The changes of body functional state of sixty submariners were monitored after one-year seafaring of combat-ready training by using Ritm-MET (Moscow, Russia) equipment. The results showed that the body functional status of submariners was relatively equal, ratio of submariner having body functional state that meet requirements of occupational health was remained pretty high (> 90%). After one-year seafaring of combat-ready training, the results showed that: the heart rate, and Hildebrant index, and TI index increased higher than those of them before one-year seafaring of combat-ready training (67.0±1.0 vs 72.0±1.0), (4.16±0.11 vs 4.30±0.10), (87.17±9.65 vs 135.0±12.0), respectively and exceeding the permitted limitation (30÷120). Thereby, in conclusion, body functional state was decreased by intensity and stress of one-year seafaring of combat-ready training, especially the cardiovascular regulation of central nervous system.